(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This paper contains an in-depth study of conjunctions, including their meaning, types as well as uses or functions in English. Conjunctions are words that link or connect two words, phrases, clauses or sentences together, either in speech or in writing. Conjunctions are one of the eight parts of speech in English, according to the traditional grammar. Apart from the coordinating, subordinating and correlative types, the author has also researched into other kinds of conjunctions that can be of great interest to the reader. The author deemed it necessary to carry out a study of this kind because over the years, this important area of language study has received less attention from language scholars and students of English/linguistics in comparison with other parts of speech like nouns, verbs, adjectives and prepositions. As this paper had unveiled, the author had not only conceived of conjunctions as one of the eight parts of speech in English, as upheld in traditional grammar, but also went beyond to examine the meaning and uses of conjunctions semantically and pragmatically as well as in propositional logic. This study is very significant, as it provides an impetus for those who hitherto have not thought of researching into this area of language study. Furthermore, the paper has presented before the reader a myriad of sentential examples for easy understanding or comprehension.